Tourism;Concepts,Issues and Impacts - Dilip kumar das (Sage, 2019)
This textbook provides a thorough understanding of the conceptual framework of tourism. It offers a comprehensive overview of the key concepts and terms used in the tourism industry, various agencies involved, tourism-related laws, demand and supply dimensions and the economic, socio-cultural and environmental effects of tourism activities.